Causes of Death in Different Subtypes of Ischemic and Hemorrhagic Stroke. (August 2018) - Liu, Chi-Hung; Lin, Jr-Rung; Liou, Chia-Wei; Lee, Jiann-Der; Peng, Tsung-I; Lee, Meng; Lee, Tsong-Hai
Causes of death in both ischemic stroke (IS) and hemorrhagic stroke (HS) subtypes are not comprehensively studied. Between 2008 and 2011, we enrolled 11 215 first-ever stroke patients from the Stroke Registry of Chang-Gung Healthcare System and linked these data to the national death registry. The main causes of death in each stroke subtype were assessed. Patients with HS had higher overall mortality than IS (32.0% vs 18.1%, P < .001). In IS subtypes, large-artery atherosclerosis plus cardioembolism had the worst mortality (40.7%, P < .001). Stroke was the leading cause of death in both IS and HS within the first year. Stroke remained the major cause of death in HS, but cancer was the leading cause of death in IS after the first year. After excluding the patients with previous cancer history, cancer was still an important cause of death in IS and HS, particularly in the IS subtypes of small vessel occlusion, stroke of undetermined etiology, and transient ischemic attack.